1998
DOI: 10.1007/bf03347339
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in free-fatty acids (FFA) do not alter serum leptin levels

Abstract: Leptin, the product of the ob gene, is a recently discovered hormone secreted by adipocytes. Serum leptin concentrations increase in correlation with the percentage of body fat, but besides that little is known about the physiological actions of leptin in humans. The aim of this study was to assess the influence of changes in circulating free-fatty acids on serum leptin levels. Increases in plasma FFA levels (p < 0.02) were obtained in a group of normal subjects following the administration of intralipid plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
14
1
Order By: Relevance
“…This in line with two in vivo studies, where changes of plasma FFA induced by acipimox or lipid infusion did not correlate with changes in plasma leptin in normal and abdominally obese subjects (21,22), but contrasts with a recent in vitro study reporting down-regulation of both leptin protein and mRNA by FFA (24). Different composition of plasma FFAs could help to explain the divergent results of the above discussed studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This in line with two in vivo studies, where changes of plasma FFA induced by acipimox or lipid infusion did not correlate with changes in plasma leptin in normal and abdominally obese subjects (21,22), but contrasts with a recent in vitro study reporting down-regulation of both leptin protein and mRNA by FFA (24). Different composition of plasma FFAs could help to explain the divergent results of the above discussed studies.…”
Section: Discussionsupporting
confidence: 80%
“…However, the role of FFAs on leptin secretion in animals and humans is not clear at present, because no effect (21)(22)(23), inhibition (24), or even stimulation (25) is reported. Interpretation of some of these results is limited by the increase in insulin secretion typically occurring during lipid infusion (20).…”
Section: Introductionmentioning
confidence: 98%
“…10 Low leptin concentrations could be therefore lead to triglyceride accumulation in pancreatic islets which contributes to b-cell dysfunction 40 as well as to elevation of plasma concentrations of free fatty acids which in turn induce insulin resistance in skeletal muscle. 41 Although shortterm changes in plasma FFA induced by lipid infusion and Acipimox did not affect plasma leptin concentrations, 42 it cannot be ruled out that long-term alterations of lipolysis could modulate leptin secretion.…”
Section: Discussionmentioning
confidence: 96%
“…In accord with these results, 5 h of lipid infusion resulted in increased leptin mRNA concentrations in subcutaneous fat of healthy volunteers (35). In two other human studies no change in leptin levels was found after a short time (2 or 3 h) of lipid infusion (45,46) or after an additional 3 h of lipid infusion in combination with a hyperglycaemic, hyperinsulinaemic clamp (45). Hennes et al (45) found that acipimox treatment (1750 mg in 8 h) lowered FFA and increased plasma leptin concentrations after a hyperglycaemic, The AUC (plasma concentration´24 h) for glucose, insulin, triglycerides and FFA (mean 6 S.E.)…”
Section: Discussionmentioning
confidence: 99%